Prevalence of Body Mass Index and Associated with Demographic Factors among Pakistan School-Aged Adolescents - Moazzam Tanveer, Nadeem Roy, Asifa Zeba, Sajjad Haider, Naif S. Albarha, Nayab Tanveer, Mubashar Ali, Umar Tanveer (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the most recent estimates of underweight, overweight, and obesity prevalence in Pakistani school-aged adolescents aged 12 to 17 years, Methods: A cross-sectional study was conducted using a convenience sampling approach with 2100 Pakistani from 24 schools in central Punjab province. The CDC US 2000 was used to define underweight < 5th percentile, overweight > 85th to < 95th percentile, and obese equal or greater than 95th percentile, the Chi-square test was used. The Pearson correlation coefficient (r) was used to determine the correlation. The statistical significance level was set at p < 0.05. Results: prevalence of underweight U/W, overweight O/W, and obesity O/B was (21.9%, 5.8%, and 5.4%, respectively. The BMI had a positive relationship with gender, residency school kind and school level. Conclusion: Underweight, overweight, and obesity were prevalent among Pakistani school-aged adolescents. Girls were significantly more than boys to be overweight and obese. Students in urban regions were more likely than those in rural areas to be overweight. The relationship between BMI, behavioral, and other health variables should also be investigated in future research using longitudinal or interventional approaches.